2010
DOI: 10.1007/s00792-009-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, purification and characterisation of a recombinant purine nucleoside phosphorylase from Bacillus halodurans Alk36

Abstract: A purine nucleoside phosphorylase from the alkaliphile Bacillus halodurans Alk36 was cloned and overexpressed in Escherichia coli. The enzyme was purified fivefold by membrane filtration and ion exchange. The purified enzyme had a Vmax of 2.03 × 10−9 s −1 and a Km of 206 μM on guanosine. The optimal pH range was between 5.7 and 8.4 with a maximum at pH 7.0. The optimal temperature for activity was 70°C and the enzyme had a half life at 60°C of 20.8 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have shown that PNP exhibits a pH optimum of 7.0, retaining >70% activity between pH 5 and 9 (Visser et al, 2010a). In the current study UP, in dilute substrate solutions, was found to show a pH optimum of 7.0, retaining 60% activity between pH 6.0 and 8.2.…”
Section: Influence Of Reaction Medium Phmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown that PNP exhibits a pH optimum of 7.0, retaining >70% activity between pH 5 and 9 (Visser et al, 2010a). In the current study UP, in dilute substrate solutions, was found to show a pH optimum of 7.0, retaining 60% activity between pH 6.0 and 8.2.…”
Section: Influence Of Reaction Medium Phmentioning
confidence: 97%
“…It was postulated that the poor reaction performance was a result of mechanical denaturation of the enzymes as a result of a high-shear environment caused by the radial impeller at 1250 rpm (Colombié et al, 2001), in combination with the high solids loading. This sensitivity to physical denaturation is possibly a consequence of both the biocatalysts being multi-subunit enzymes (Visser et al, 2010a;Leer et al, 1977) and therefore prone to mechanical effects. Consequently, a milder and more effective agitation configuration was evaluated.…”
Section: Influence Of Reactor Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Its ability to transfer glycosyl residues to acceptor bases is of great biotechnological interest owing to its potential application in the synthesis of nucleoside analogues used in the treatment of antiviral infections and in anticancer chemotherapy (Li et al, 2008;Nannemann et al, 2010;Visser et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several purine nucleoside analogues have been clinically investigated as potential drugs for the treatment of leukaemia and lymphoma (Ravandi & Gandhi, 2006). However, the production of these molecules still has a high manufacturing cost and faces some challenges such as the low solubility and poor reaction kinetics of the reagents (Visser et al, 2010;Pinheiro et al, 2008). Thus, there is an urgent need to find ways to increase the cost-effectiveness of the synthesis of purine nucleoside analogues.…”
Section: Introductionmentioning
confidence: 99%